Characterization of muscarinic receptor subtypes inhibiting Ca2+ current and M current in rat sympathetic neurons. - Bernheim, L (1992)
Muscarinic receptors mediating suppression of Ca2+ current and of M-type K+ current in rat superior cervical ganglion neurons were subclassified pharmacologically by using the muscarinic receptor antagonists pirenzepine and himbacine. Our voltage clamp experiments previously distinguished fast and slow intracellular signaling pathways coupling muscarinic receptors to calcium channels. We now establish that the fast, pertussis toxin-sensitive suppression of Ca2+ current is mediated primarily by muscarinic receptors of the M4 subtype, whereas the slow, bis(2-aminophenoxy)-ethane-N,N,N',N'-tetraacetate (BAPTA)-sensitive suppression of Ca2+ current is mediated primarily by muscarinic receptors of the M1 subtype. Both actions on Ca2+ current are blocked by guanosine 5'-[beta-thio]diphosphate. Muscarinic suppression of M current is slow, BAPTA-sensitive, and mediated by receptors of the M1 subtype. Hence the two muscarinic pathways use different receptors and different guanine nucleotide binding proteins to produce different actions on channels.